Five Love Languages and Personality Factors Revisited - Edwin Adrianta Surijah; Komala Sari (ANIMA Indonesian Psychological Journal, 2018)
Current research replicates previous research on five love languages. It aimed to gather further validation evidence and to determine whether a person with a particular love language has a certain personality type as well. Undergraduate students participated as research sample (n = 313). Love languages and personality types were measured with Five Love Languages scale and Big Five Inventory respectively. Zero-order correlation showed a significant correlation between love languages and personality types except on Receiving Gift and Neuroticism. Comparison with the previous research exhibited diverging result which prompts to discussions on a better approach to measuring love languages.